A portable immunomagnetic cell capture system to accelerate culture diagnosis of bacterial infections. Issue 11 (27th April 2016) - Singh, Saurabh; Upadhyay, Mohita; Sharma, Jyoti; Gupta, Shalini; Vivekanandan, Perumal; Elangovan, Ravikrishnan
Abstract : An affordable immuno-magnetic cell capture system for bacterial detection in 7 hours with 10 CFU ml −1 sensitivity. Abstract : Bacterial infections continue to be a major cause of deaths globally, particularly in resource-poor settings. In the absence of rapid and affordable diagnostic solutions, patients are mostly administered broad spectrum antibiotics leading to antibiotics resistance and poor recovery. Culture diagnosis continues to be a gold standard for diagnosis of bacterial infection, despite its long turnaround time of 24 to 48 h. We have developed a portable immunomagnetic cell capture (iMC 2 ) system that allows rapid culture diagnosis of bacterial pathogens. Our approach involves the culture growth of the blood samples in broth media for 6 to 8 h, followed by immunomagnetic enrichment of the target cells using the iMC 2 device. The device comprises a disposable capture chip that has two chambers of 5 ml and 50 μl volume connected through a channel with a manual valve. Bacterial cells bound to antibody coated magnetic nanoparticles are swept from the 5 ml sample chamber into the 50 μl recovery chamber by moving an external magnetic field with respect to the capture chip using a linear positioner. This enables specific isolation and up to 100× enrichment of the target cells. The presence of bacteria in the recovered sample is confirmed visually using a lateral flow immunoassay. The system is demonstrated in buffer and blood samples spiked with S. typhi . The method has high sensitivity (10 CFU ml −1 ), specificity and a rapid turnaround time of less than 7 h, a significant improvement over conventional methods.